Is the algorithm used to process heart rate variability data clinically relevant? Analysis in male adolescents - Germano Soares, Antonio Henrique; Farah, Breno Quintella; Cucato, Gabriel Grizzo; Albanez Bastos-Filho, Carmelo Jose; Destro Christofaro, Diego Giulliano [UNESP]; Marques Vanderlei, Luiz Carlos [UNESP]; Rodrigues de Andrade Lima, Aluisio Henrique; Ritti-Dias, Raphael Mendes (Inst Israelita Ensino & Pesquisa Albert Einstein, 2016)
Objective: To analyze whether the algorithm used for the heart rate variability assessment (fast Fourier transform versus autoregressive methods) influenced its association with cardiovascular risk factors in male adolescents. Methods: This cross-sectional study included 1,152 male adolescents (aged 14 to 19 years). The low frequency, high frequency components (absolute numbers and normalized units), low frequency/high frequency ratio, and total power of heart rate variability parameters were obtained using the fast Fourier transform and autoregressive methods, while the adolescents were resting in a supine position. Results: All heart rate variability parameters calculated from both methods were different (p<0.05). However, a low effect size (<0.1) was found for all parameters. The intra-class correlation between methods ranged from 0.96 to 0.99, whereas the variation coefficient ranged from 7.4 to 14.8%. Furthermore, waist circumference was negatively associated with high frequency, and positively associated with low frequency and sympatovagal balance (p<0.001 for both fast Fourier transform and autoregressive methods in all associations). Systolic blood pressure was negatively associated with total power and high frequency, whereas it was positively associated with low frequency and sympatovagal balance (p<0.001 for both fast Fourier transform and autoregressive methods in all associations). Body mass index was negatively associated with high frequency, while it was positively associated with low frequency and sympatovagal balance (p values ranged from <0.001 to 0.007). Conclusion: There are significant differences in heart rate variability parameters obtained with the fast Fourier transform and autoregressive methods in male adolescent; however, these differences are not clinically significant.
Keywords: Autonomic nervous system; Adolescent; Heart rate/physiology; Cardiovascular system